SNF2L maintains glutathione homeostasis by initiating SLC7A11 transcription through chromatin remodeling - Jiaguan Zhang; Zeshou Gao; Yi Yang; Zhenhao Li; Binjie Wu; Chunxin Fan; Yuyan Zheng; Ruohan Yang; Fangrong Zhang; Xiaohuang Lin; Daoshan Zheng (Cell Death and Disease)
Abstract SNF2L encodes an ISWI chromatin remodeling factor that promotes gene transcription and is consistently elevated in cancers. Previous studies have shown that inhibiting SNF2L expression in cancer cells leads to significant growth suppression, DNA damage, and cell death. However, the underlying mechanisms remain poorly understood. In this study, we demonstrated that cancer cells lacking SNF2L show significantly decreased glutathione (GSH) levels, leading to elevated reactive oxygen species (ROS) and increased oxidative stress. SNF2L deficiency also heightened the sensitivity of cancer cells to APR-246, a drug that depletes GSH and induces oxidative stress, consequently decreasing cell viability and increasing ROS levels, regardless of p53 status. Mechanistically, we found that NRF2 recruits SNF2L to the SLC7A11 promoter, leading to increased chromatin accessibility and facilitating SLC7A11 transcription. This results in decreased cystine uptake and impaired GSH biosynthesis. These findings suggest that targeting the SNF2L/SLC7A11 axis could enhance the effectiveness of APR-246 by depleting GSH and increasing ROS level in cancer cells, highlighting SNF2L as a promising therapeutic target.